Impulsive sound recognition system (I-SoRecS) - Macaso, Harvey Roy E.; Nicer, Agnes Therese M. (2007)
Recognition of impulsive sounds which relay urgent information such as alarms, human screams, or door slams is a way of being warned of possible danger in the environment. However, people who have hearing impairments need a reliable device to recognize such sounds in order for them to respond to their environment. Sound detection and recognition systems now exist for surveillance and security applications and on portable tele-assistive devices but they don't benefit the low-end market. We are developing a simple prototype of an impulsive sound recognition system. In this thesis, we present an approach to sound recognition using a mathematical concept in Linear Algebra called Least Squares Method. In this algorithm, valuable coefficients are extracted from a set of data gathered from wave files which are sound inputs from users and on a sound database containing signals distributed among three different classes (i.e. alarms, human screams, and door slams). After extracting, the algorithm uses these coefficients to compare different wave files. Thus, the goal of this study is to determine the potential of Least Squares Method as an algorithm for recognizing impulsive sounds. This approach was used in a voice recognition prototype, which recognizes an uttered letter in the English alphabet. The study showed that it was effective in comparing wave files.